THE MODERATING ROLE OF PEER SUPPORT ON LEARNING INTEREST AND LEARNING DISCIPLINE ON STUDENT LEARNING MOTIVATION IN ECONOMICS SUBJECTS IN 3T AREAS - Liubana, Alfred; Ahman, Eeng; Supardi, Endang; Kurniawati, Susanti; Kurjono, Kurjono; Majid, Mohamad Zuber Abd (UNIVERSITAS NEGERI SURABAYA, 2025)
This study investigates the moderating role of peer support on the relationship between learning interest, learning discipline, and student motivation in a 3T (frontier, outermost, and disadvantaged) region Batuputih sub-district. While previous studies have explored these variables individually, limited research has examined how peer support interacts with interest and discipline to influence learning motivation in underdeveloped regions. Employing a quantitative approach with a survey method, data were collected from 201 grade XI students at SMAN Tupan and SMAN Benlutu using purposive sampling. A 5-point Likert scale questionnaire was administered, and sample adequacy was determined using G*Power analysis (effect size = 0.15, power = 0.95, α = 0.05), resulting in a minimum requirement of 107 participants. Data were analyzed using PLS-SEM via SmartPLS. The findings indicate that both learning interest (p = 0.027) and learning discipline (p = 0.000) significantly influence student motivation. However, peer support does not moderate these relationships, as shown by p-values of 0.744 and 0.861, respectively. These results suggest that while interest and discipline are critical drivers of motivation, peer support may not play a significant moderating role in this context. This study contributes to the understanding of motivational factors in disadvantaged educational settings and provides insights for educators in designing targeted interventions.